Primary Bone Xanthoma: A Case Report - Singh, Parul; Naidu, Raji Tejas; Chaturvedi, Uma; Cherian, Susan (Annals of Pathology and Laboratory Medicine, 2021)
Xanthoma of bone is a rare disorder of bone which occurs due to cholesterol deposits in the bone. Clinically the patients usually present with pain or fracture of the affected bone. Radiologically it presents as a lytic lesion, often with cortical expansion or disruption. Xanthoma of bone is usually associated with hyperlipidemia but rare cases of non- hyperlipidemia xanthoma are also reported, termed as primary bone xanthoma. Here we present a rare case of a 46-year-old male who presented with pain and swelling in the right middle finger. X ray showed lytic lesion in the proximal phalanx of right middle finger. Laboratory tests showed normal lipid profile. Bone biopsy and histological examination is necessary for diagnosis and to differentiate it from Rosai–Dorfman disease, Langerhans cell histiocytosis and fibrous/post traumatic dysplasia, malignant fibrous histiocytoma, or metastatic renal cell carcinoma. A diagnosis of primary bone xanthoma was made based on histology and immunohistochemistry. The fracture was treated surgically. The case report emphasises the role of histology in diagnosis of this rare clinical entity.